2008
DOI: 10.1002/syn.20597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuropeptide Y Y2 receptor deletion on emotional stress‐induced neuronal activation in mice

Abstract: In different behavioral paradigms including the elevated plus maze (EPM), it was observed previously that deletion of the neuropeptide Y Y2 receptor subtype results in potent suppression of anxiety-related and stress-related behaviors. To identify neurobiological correlates underlying this behavioral reactivtiy, expression of c-Fos, an established early marker of neuronal activation, was examined in Y2 receptor knockout (Y2 −/− ) vs. wildtype (WT) mice. Mice were placed on the open arm (OA) or closed arm (CA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…In Mg 2+ deficient mice the findings of elevated abundance of prepro-CRH mRNA and ACTH release point towards an up-regulated set-point of the HPA axis during Mg 2+ deficiency which is also observed in some, but not all patients with an anxiety disorder (for review see Charney and Drevets, 2008; Young et al., 2008 ), and this is therefore suggested to contribute to the enhanced anxiety-related behaviour of Mg 2+ deficient mice. In further support of this, we observed increased neuronal activity in the PVN of Mg 2+ deficient BALB/c mice in response to the open arm of an elevated plus maze which, though considered as being mildly anxiogenic, is able to cause the release of stress hormones and to induce neuronal activation in rodents compared with an unstressed condition ( Muigg et al., 2009; Nguyen et al., 2009; Salome et al., 2004 ). Interestingly, while stress-induced neuronal activation has been shown to be blunted in cortical areas of Balb/c mice compared with C57Bl/6 mice, PVN activation is similar between the two strains ( O’Mahony et al., 2010 ) supporting the use of Balb/c mice complementary to C57Bl/6N mice in the present study.…”
Section: Discussionsupporting
confidence: 59%
“…In Mg 2+ deficient mice the findings of elevated abundance of prepro-CRH mRNA and ACTH release point towards an up-regulated set-point of the HPA axis during Mg 2+ deficiency which is also observed in some, but not all patients with an anxiety disorder (for review see Charney and Drevets, 2008; Young et al., 2008 ), and this is therefore suggested to contribute to the enhanced anxiety-related behaviour of Mg 2+ deficient mice. In further support of this, we observed increased neuronal activity in the PVN of Mg 2+ deficient BALB/c mice in response to the open arm of an elevated plus maze which, though considered as being mildly anxiogenic, is able to cause the release of stress hormones and to induce neuronal activation in rodents compared with an unstressed condition ( Muigg et al., 2009; Nguyen et al., 2009; Salome et al., 2004 ). Interestingly, while stress-induced neuronal activation has been shown to be blunted in cortical areas of Balb/c mice compared with C57Bl/6 mice, PVN activation is similar between the two strains ( O’Mahony et al., 2010 ) supporting the use of Balb/c mice complementary to C57Bl/6N mice in the present study.…”
Section: Discussionsupporting
confidence: 59%
“…The effects of rhythmic cortical stimulation on light/dark box exploration are consistent with ventral ACC involvement in regulating anxiety, fear, and stress (25)(26)(27)(28)(29), and chronic exposure to anxiety/stress induces changes in neurotransmission and longterm potentiation in the rodent ACC (26,30,31). Validation of the hypothesis linking 1-to 8-Hz cortical stimulation with increased myelination and decreased anxiety will require quantifying the generation of new oligodendrocytes and the density of myelin in mice that undergo stimulation.…”
Section: Discussionmentioning
confidence: 71%
“…Stress-induced neuronal activation is thought to delineate neuronal stress circuitries in rats and mice [22] , [39] [43] . Exposure to the OA of an EPM is considered as a mild stressor inducing higher fear/anxiety than exposure to the closed arm [44] [46] . Indeed, the present study revealed that mice stressed by OA exposure, compared to non-stressed (basal) mice, showed enhanced c-Fos expression in widespread brain regions related to fear/anxiety.…”
Section: Discussionmentioning
confidence: 99%